Pengaruh ESG terhadap Nilai Perusahaan dengan Kepemilikan Pemerintah dan Sensitivitas Industri Sebagai Variabel Pemoderasi - Nofrian, Mero Ruddi; Sebrina, Nurzi (Universitas Negeri Padang, 2024)
The research aims to determine whether environmental, social, and governance (ESG) scores influence company value with government ownership and industry sensitivity as moderating variables by testing moderated regression analysis (MRA Test) using the eviews version 12 application. The population is companies included in the LQ45 index on the Indonesia Stock Exchange from 2020-2022. The sampling technique used was purposive sampling, there were 26 companies used as research samples. The data used is secondary data in the form of ESG scores from Revinitif Eikon, equity market value, total liabilities, and total assets obtained from the official website of the Indonesia Stock Exchange, namely www.idx.co.id and the official websites of related companies. The results show that the ESG of companies included in the LQ45 index on the IDX has negative effect on firm value. Government ownership weakens the relationship between ESG and the value of companies included in the LQ45 index on the IDX. Industry sensitivity strengthens the relationship between ESG and the value of companies included in the LQ45 index on the IDX. Hopefully, this research can provide an overview of considering aspects that need to be taken into account in investment that are not only seen in monetary measures.